2016
DOI: 10.3389/fpls.2016.00850
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Evaluations of Quinoa: Preliminary Results from Post International Year of Quinoa FAO Projects in Nine Countries

Abstract: Chenopodium quinoa Willd., a high quality grain crop, is resistant to abiotic stresses (drought, cold, and salt) and offers an optimal source of protein. Quinoa represents a symbol of crop genetic diversity across the Andean region. In recent years, this crop has undergone a major expansion outside its countries of origin. The activities carried out within the framework of the International Year of Quinoa provided a great contribution to raise awareness on the multiple benefits of quinoa as well as to its wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 54 publications
2
119
1
8
Order By: Relevance
“…Puno and cv. Titicaca [10,27], were chosen to evaluate the agronomic performance of commercially available quinoa cultivars. Since these cultivars were created by the same breeder (Table 1), and therefore could have similar selection criteria regarding the originally used landraces, we additionally examined another registered European quinoa cultivar (cv.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Puno and cv. Titicaca [10,27], were chosen to evaluate the agronomic performance of commercially available quinoa cultivars. Since these cultivars were created by the same breeder (Table 1), and therefore could have similar selection criteria regarding the originally used landraces, we additionally examined another registered European quinoa cultivar (cv.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Parents were mostly chosen based on multi-environment long-term results for seed yield, seed size, sensitivity against photoperiod, tolerance to lodging, drought tolerance, or pre-harvest sprouting resistance [24]. However, despite complex interactions between genotypic properties and environmental factors, quinoa breeding programs mainly focused on cultivars producing high yields [25][26][27]. Even though, some studies highlighted abiotic factors to influence the nutritional profile of quinoa seeds [28][29][30], there is little information on quality of different European quinoa cultivars or rather the mechanisms triggering quality changes [3,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they indicated that the Q-52 variety responds to the drought by closing the stomata and also reducing the leaf area to decline the transpiration rate. On the other hand, Regalona proved to be more tolerant to the drought stress due to the fact that it was produced by cross breeding of genotypes from two different sources, one close to the equator (low altitude) and the other one from southern Chilean region ( low levels of rain) (Bazile et al, 2016).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Globally, FAO evaluated the performance of 21 quinoa genotypes in 26 countries representing 19 agrarian systems. Results indicated that landraces Q21 and Q26 were more stable with a satisfactory yield (> 1 t/ha) across the different environments (Bazile et al, 2016). The genotype by environment interaction is analyzed by statistical methods to describe G x E data (van Eeuwijk et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation